Fermentation profile, cholesterol-reducing properties and chemopreventive potential of β-glucans from Levilactobacillus brevis and Pediococcus claussenii – a comparative study with β-glucans from different sources. Issue 21 (29th September 2021) - Schlörmann, W.; Bockwoldt, J. A.; Mayr, M. F.; Lorkowski, S.; Dawczynski, C.; Rohn, S.; Ehrmann, M. A.; Glei, M.
Abstract : β-glucans from the lactic acid bacteria L. brevis and P. claussenii as well as β-glucans from oat, barley, yeast, and curdlan were analyzed regarding their cholesterol-binding capacity, fermentation profile, and chemopreventive potential. Abstract : The aim of the present study was to investigate whether β-glucans obtained from the lactic acid bacteria (LAB) Levilactobacillus (L.) brevis and Pediococcus (P.) claussenii exhibit similar physiological effects such as cholesterol-binding capacity (CBC) as the structurally different β-glucans from oat, barley, and yeast as well as curdlan. After in vitro fermentation, fermentation supernatants (FSs) and/or -pellets (FPs) were analyzed regarding the concentrations of short-chain fatty acids (SCFAs), ammonia, bile acids, the relative abundance of bacterial taxa and chemopreventive effects (growth inhibition, apoptosis, genotoxicity) in LT97 colon adenoma cells. Compared to other glucans, the highest CBC was determined for oat β-glucan (65.9 ± 8.8 mg g −1, p < 0.05). Concentrations of SCFA were increased in FSs of all β-glucans (up to 2.7-fold). The lowest concentrations of ammonia (down to 0.8 ± 0.3 mmol L −1 ) and bile acids (2.5–5.2 μg mL −1 ) were detected in FSs of the β-glucans from oat, barley, yeast, and curdlan. The various β-glucans differentially modulated the relative abundance of bacteria families and reduced the Firmicutes/Bacteroidetes ratio. Treatment of LT97 cells with the FSs led to a significant dose-dependent growth reduction and increase in caspase-3 activity without exhibiting genotoxic effects. Though the different β-glucans show different fermentation profiles as well as cholesterol- and bile acid-reducing properties, they exhibit comparable chemopreventive effects.